1970
DOI: 10.1115/1.3451441
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for the Rupture of a Lubricating Film. Part I: Theoretical Model

Abstract: The shape of the film-vapor interface is found for a thin liquid film separating from a stationary surface and being swept away on an opposing moving surface. The analysis is for two-dimensional Newtonian flow, and includes the effects of gravity, inertia, and surface tension. The principal assumption is that of a quadratic tangential velocity distribution across the film. The solution shows that the entire separation phenomenon is completed in a distance of about one plate clearance from the stagnation point.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
76
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 0 publications
1
76
0
Order By: Relevance
“…Dowson and Taylor [11] concluded that for lightly loaded lubricated contacts, represented by a cylinderon-plane conjunction, flow separation is the major mechanism determining the cavity location. For lightly loaded journal bearings, operating at low eccentricity ratios, the use of Coyne and Elrod [14,15] separation boundary condition appears to lead to better predictions. At lower eccentricity ratios, there is considerable lubricant flow between cavities and hence Floberg's rupture conditions show better agreement with experimental observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dowson and Taylor [11] concluded that for lightly loaded lubricated contacts, represented by a cylinderon-plane conjunction, flow separation is the major mechanism determining the cavity location. For lightly loaded journal bearings, operating at low eccentricity ratios, the use of Coyne and Elrod [14,15] separation boundary condition appears to lead to better predictions. At lower eccentricity ratios, there is considerable lubricant flow between cavities and hence Floberg's rupture conditions show better agreement with experimental observations.…”
Section: Introductionmentioning
confidence: 99%
“…They discussed three main modelling approaches, based on contact outlet boundary conditions. One is the traditional lubricant film rupture boundary conditions, proposed by Reynolds/Swift-Stieber [8,9], the others being the JFO (Jakobsson-Floberg [12], Olsson [13]) boundary conditions and Coyne and Elrod's separation condition [14,15]. The JFO boundary conditions are based upon the principle of conservation of mass flow beyond the point of lubricant film rupture point into a cavitation region in the form of striations.…”
Section: Introductionmentioning
confidence: 99%
“…Brewe [3] uses the Elrod algorithm to predict vapor cavitation in a submerged journal bearing during steady state and transient conditions. Vijayaraghavan and Keith [15] proposed a finite differenced scheme to predict the pressure distribution along the contact and validated the numerical results with Coyne and Elrod's experiments [20]. Yang and Keith [21] extended this approach to the piston ring lubrication, while Cioc and Keith [22] applied Elrod's algorithm using the Conservation Element (CE) and Solution Element (SE) method.…”
Section: Introductionmentioning
confidence: 99%
“…It typically occurs when the lubricant enters a region in which the film thickness increases, with a concomitant decrease in pressure, and it leads to a variety of free boundary models [4,7,8,10,17]. It also occurs in 'negative squeeze films', in which the faces of a squeeze-film bearing are moved apart from each other.…”
Section: Introductionmentioning
confidence: 99%